MENUMBUHKAN MORAL AGAMA MELALUI METODE MENDONGENG SAMBIL BERMAIN - Armanila Armanila; Riska Yanti; Fatimah Sitepu; Rahmayani Nasution; Eli Asni; Nabila Zahra; Ika Permatasari; Siti Mardiana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Early childhood is a crucial period, often referred to as the